Biochemical responses in mice induced by saxitoxins extracted from the cockles Acanthocardia tuberculatum: Biochemical responses in mice induced by saxitoxins - Takati, Nadia; Azeddoug, Houssine; Benchekroun, Mohammed Nabil; Blaghen, Mohamed; Ennaji, Moulay Mustapha (Cellular and Molecular Biology, 2023)
Harmful algae blooms have increased in frequency and geographic range in recent decades, and they produce toxins strains such as saxitoxins (STXs). they block voltage-gated sodium channels and can lead to several poisonings and the death of organisms that pose a significant risk to public and environmental health. The study of STXs toxicity has been carried out but little is known about the response of antioxidant enzymes activities to STXs in mice. The purpose of this study was to evaluate biochemical responses and oxidative stress induced by STXs extracted from Acanthocardia tuberculatum. To this end, daily, mice were treated orally for 7 days with sublethal concentrations (10 mg/100 g mouse). The animal’s liver was assessed using biomarkers such as activities of catalase (CAT), thiobarbituric acid reactive substances (TBARS), glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and succinate dehydrogenase (SDH). In the blood, plasmatic markers were analysed as glutamic oxalic transaminase (GOT), glutamic pyruvic transaminase (GPT), creatinine phosphokinase (CPK), lactate dehydrogenase (LDH), urea and creatinine. Globally, test toxicity test showed a significant decrease in the weight at 10 mg /100 g mouse, and the results showed an increase of GPT, GOT, CPK, LDH, CAT and TBARS activities and the inhibitory effect of GAPDH activities but creatinine, urea and SDH activities showed no significative difference from the control. We concluded that STXs induce oxidative stress breaking in mice the balance of the defence system and causing oxidations reactions. Moreover, STXs affect energy metabolism in mice, however, renal function in mice is not affected by exposure to STXs.